PWWP2A - a novel H3K36me3 reading component of the NuRD complex - Zhang, T (2016)
Epigenetic regulation of gene expression is critical for lineage determination during development and the stable transmission of cellular identity through cell growth and division. Chromatin modifiers are a varied group of enzymes that regulate patterns of gene expression through the modification of DNA and histones. Epigenetic modifications alter the physical structure of chromatin or recruit effectors to promote or inhibit transcription. In this study, I examined the role of pre-existing histone modifications on the activity of Polycomb and Trithorax chromatin modifying enzymes. Additionally, identification of a novel H3K36me3-reader PWWP2A may constitute a new histone crosstalk pathway between H3K36me3 and histone deacetylation. Polycomb and Trithorax proteins are two important families of transcriptional regulators that promote gene repression and activation respectively. In this study, I find that histone crosstalk between Polycomb complexes PRC1 and PRC2 promote one another’s activity while inhibiting Trithorax function. Recombinant nucleosomes carrying the PRC2 modification H3K27me3 stimulates the activity of CBX-PRC1, and nucleosomes with the PRC1 modification H2AK119u1 stimulates the activity of JARID2-PRC2. H2AK119u1 negatively regulates Trithorax activity and inhibits both the H3K4 methyltransferases MLL1/4 and the H3K36 methyltransferase NSD2. Histone crosstalk appears to be an important mechanism in the regulation of the recruitment and activity of chromatin modifiers. I identified a novel H3K36me3 binding protein PWWP2A in an unbiased screen for readers of H3K27me3 and H3K36me3. Biochemical characterisation of PWWP2A in HeLa cells and mouse embryonic stem cells (mESCs) showed that PWWP2A interacts with NuRD subunits MTA1-3, HDAC1/2, and RBBP4/7. Genome-wide mapping of PWWP2A targets in mESCs shows that it is enriched over the gene bodies of highly transcribed genes sharing many gene targets with HDAC1. PWWP2A localisation correlates highly with H3K36me3, and its localisation at gene bodies is dependent on the putative H3K36me3-binding PWWP domain. In budding yeast, H3K36me3-mediated recruitment of the yeast HDAC complex Rpd3S is important for maintaining transcriptional integrity over coding regions. PWWP2A-NuRD may represents an analogous pathway of transcriptional regulation in mammalian organisms.